Pengambilan Keputusan Etis Konsultan Pajak: Ethical Sensitivity, Ethical Judgment dan Self Efficacy - Syahbana, Khairuni; Ratnawati, Vince; Wahyuni, Nita (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study aims to analyze the influence of ethical sensitivity, ethical judgement, and self-efficacy on ethical decision-making. The respondents were tax consultants with a total of 44 people as the primary data source. The study used Multiple Linear Regression analysis. It was found that the variables of ethical sensitivity, ethical judgment and self efficacy had a positive effect on ethical decision-making. A person is able to understand and interpret ethically, evaluate his or her personal regarding ethical or not actions, as well as the belief in organizing and taking action to accomplish a particular task. So that decisions can be held accountable in accordance with ethics. Tax consultants apply a directed interpretation of ethical issues, and are able to make correct assessments objectively, professionally, and fairly. Tax consultants must also do their job well so that decisions will be ethical. Not only Auditors, Lecturers, Accountants, or Consumers who make ethical decisions, but as tax consultants must instill ethics in their decision-making.